Constructing a chaos proofing pre-development framework to manage chaos in a chaos-prone systems development environment - Othman M.; Zin A.M.; Hamdan A.R. (2023)
When plans are disrupted to accommodate changes in a software development project, the environment becomes unstable. This brings about chaos. "Chaos" is real and we need to deal with it. This research is based on the premise that I. Chaos has a pattern, and that it is possible to learn this pattern and 2. If we are able to measure chaos, we will be able to better manage the situation brought by chaos. This paper put forth a list of chaos triggers based on findings from a case study of a chaos-prone system development project based in Malaysia. Lessons learned based on findings from a focus-group depth interview leads to the construction of a Pre Development Framework to chaos-proof system development environment. 2008 IEEE.